Neuron-Type Specific Functions of DNT1, DNT2 and Spz at the Drosophila Neuromuscular Junction - Sutcliffe, Ben; Forero, Manuel G.; Zhu, Bangfu; Robinson, Iain M.; Hidalgo, Alicia (PLOS ONE, 2013)
Retrograde growth factors regulating synaptic plasticity at the neuromuscular junction (NMJ) in Drosophila have long been predicted but their discovery has been scarce. In vertebrates, such retrograde factors produced by the muscle include GDNF and the neurotrophins (NT: NGF, BDNF, NT3 and NT4). NT superfamily members have been identified throughout the invertebrates, but so far no functional in vivo analysis has been carried out at the NMJ in invertebrates. The NT family of proteins in Drosophila is formed of DNT1, DNT2 and Spätzle (Spz), with sequence, structural and functional conservation relative to mammalian NTs. Here, we investigate the functions of Drosophila NTs (DNTs) at the larval NMJ. All three DNTs are expressed in larval body wall muscles, targets for motor-neurons. Over-expression of DNTs in neurons, or the activated form of the Spz receptor, Toll10b, in neurons only, rescued the semi-lethality of spz2 and DNT141, DNT2e03444 double mutants, indicating retrograde functions in neurons. In spz2 mutants, DNT141, DNT2e03444 double mutants, and upon over-expression of the DNTs, NMJ size and bouton number increased. Boutons were morphologically abnormal. Mutations in spz and DNT1,DNT2 resulted in decreased number of active zones per bouton and decreased active zone density per terminal. Alterations in DNT function induced ghost boutons and synaptic debris. Evoked junction potentials were normal in spz2 mutants and DNT141, DNT2e03444 double mutants, but frequency and amplitude of spontaneous events were reduced in spz2 mutants suggesting defective neurotransmission. Our data indicate that DNTs are produced in muscle and are required in neurons for synaptogenesis. Most likely alterations in DNT function and synapse formation induce NMJ plasticity leading to homeostatic adjustments that increase terminal size restoring overall synaptic transmission. Data suggest that Spz functions with neuron-type specificity at the muscle 4 NMJ, and DNT1 and DNT2 function together at the muscles 6,7 NMJ.